MEMUDARNYA KEPEMIMPINAN POLITIK ULAMA - Arif Rohman (LPPM UNY, 2002)
Abstract The involvement of ulama in the election organized by New Order since 1971 to1997 almost constantly showed positive result, especially in increasing the number of contestant vote. However what happened in 1999election was on the contrary. The objective of study in thus: first, to describe the process of the political leadership of ulama in political parties; second, to investigate the characteristics of the political leadership of ulama; third, to find out the causal factors of the fading submissiveness of people to the political leadership of ulama. Using behaviorism approach the data collected consist of verbal data, document data and occurrences record. The data is collected through: (1) in-depth interview of 35 subjects sampled out purposively; (2) observation and (3)the study of written data of local KIPP and PPD; with the triangulation of method variation, situation variation and data source variation. The place of the study of Sewon and Pleret subdistrics represents Bantul regency of Special DIstric of Yogyakarta. The data is analyzed qualitatively using “flow” model. Finally the resut of the study are (1) the majority of ulama has conducted their leadership as the chairmen and board members of politic parties in democratic way(2) The characteristic of their leadership is considered to be ‘active-negative’. (3)the causal factors of the fading submissiveness of people to the political leadership of ulama are: the economic burden of the people as a result of the crisis, mass media information, the increasingly high education level of the people, the growing rationalistic consideration of the people. Keywords: Leadership of Ulama, Political Party, election, and fading Submissiveness.